Understanding aerodynamics : arguing from the real physics - McLean, Doug, 1943- (Chichester : Wiley-Blackwell, 2013)
"Much-needed, fresh approach that brings a greater insight into the physical understanding of aerodynamicsBased on the author's decades of industrial experience with Boeing, this book helps students and practicing engineers to gain a greater physical understanding of aerodynamics. Relying on clear physical arguments and examples, Mcleanprovides a much-needed, fresh approach to this sometimes contentious subject without shying away from addressing "real" aerodynamic situations as opposed to the oversimplified ones frequently used for mathematical convenience. Motivated by the belief that engineering practice is enhanced in the long run by a robust understanding of the basics as well as real cause-and-effect relationships that lie behind the theory, he provides intuitive physical interpretations and explanations, debunking commonly-held misconceptions and misinterpretations, and building upon the contrasts provided by wrong explanations to strengthen understanding of the right ones. Provides a refreshing view of aerodynamics that is based on the author's decades of industrial experience yet is always tied to basic fundamentals. Provides intuitive physical interpretations and explanations, debunking commonly-held misconceptions and misinterpretations Offers new insights to some familiar topics, for example, what the Biot-Savart law really means and why it causes so much confusion, what "Reynolds number" and "incompressible flow" really mean, and a real physical explanation for how an airfoil produces lift. Addresses "real" aerodynamic situations as opposed to the oversimplified ones frequently used for mathematical convenience, and omits mathematical details whenever the physical understanding can be conveyed without them."--
Introduction to the Conceptual Landscape -- From Elementary Particles to Aerodynamic Flows -- Continuum Fluid Mechanics and the Navier-Stokes Equations -- Boundary Layers -- General Features of Flows around Bodies -- Drag and Propulsion -- Lift and Airfoils in 2D at Subsonic Speeds -- Lift and Wings in 3D at Subsonic Speeds -- Theoretical Idealizations Revisited -- Modeling Aerodynamic Flows in Computational Fluid Dynamics.
Includes bibliographical references and index.
Print version record.
Keywords: Aerodynamics; Aerodynamics; TRANSPORTATION -- Aviation -- General; Aerodynamics; Aerodynamics; Electronic books